The abandoned empress. 9 - In-a; Yuna; Yuna (Yen Press, 2024)
"After six long years, Tia's goal of becoming an official knight finally comes true. And as an official knight, she now has the ability to make a "Blood Oath" to the emperor--and in doing so, surrender her right to the throne. Despite the crown prince's continued attempts to thaw her frozen heart, Tia is determined to free herself from the noble faction's schemes and the grim fate she's desperately tried to flee from...but that resolve is soon shaken when she finds Ruveliss in danger. Will Tia allow Fate to shape her future? Or will she finally take her destiny into her own hands?"--Back cover.